Gut microbiome derived short chain fatty acids: Promising strategies in necrotising enterocolitis - María P Cifuentes; Jonathan A Chapman; Christopher J Stewart (Current Research in Microbial Sciences, 2024)
Necrotising enterocolitis (NEC) is a devastating condition that poses a significant risk of morbidity and mortality, particularly among preterm babies. Extensive research efforts have been directed at identifying optimal treatment and diagnostic strategies but results from such studies remain unclear and controversial. Among the most promising candidates are prebiotics, probiotics and their metabolites, including short chain fatty acids (SCFAs). Such metabolites have been widely explored as possible biomarkers of gut health for different clinical conditions, with overall positive effects on the host observed. This review aims to describe the role of gut microbiome derived SCFAs in necrotising enterocolitis. Until now, information has been conflicting, with the primary focus on the main three SCFAs (acetic acid, propionic acid, and butyric acid). While numerous studies have indicated the relationship between SCFAs and NEC, the current evidence is insufficient to draw definitive conclusions about the use of these metabolites as NEC biomarkers or their potential in treatment strategies. Ongoing research in this area will help enhance both our understanding of SCFAs as valuable indicators of NEC and their practical application in clinical settings.